The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jper.20-0187
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microbiota in overweight and obese young adults with no destructive periodontal disease

Abstract: Background This study analyzed the levels of a specific group of periodontal health/disease‐related oral bacteria in the subgingival biofilm of young adults with overweight (OW) and obesity (OB), and no destructive periodontal disease. Methods Full‐mouth periodontal assessment and subgingival biofilm sampling were performed in individuals with normal weight (NW) (BMI [body mass index] ≥18.5 to ≤24.9 kg/m2; n = 29), OW (BMI ≥25 to ≤29.9 kg/m2; n = 26), or OB (BMI ≥30 kg/m2; n = 22). BMI, waist (WC) and hip (HC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…These results also revealed no significant associations between clinical variables that were previously observed, such as increased prevalence in the presence of orthodontic brackets [12][13][14] and associations with higher BMI [15][16][17]. The lack of significant associations between these clinical variables and the presence of S. noxia may be due to the overall sample size of this pilot study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…These results also revealed no significant associations between clinical variables that were previously observed, such as increased prevalence in the presence of orthodontic brackets [12][13][14] and associations with higher BMI [15][16][17]. The lack of significant associations between these clinical variables and the presence of S. noxia may be due to the overall sample size of this pilot study.…”
Section: Discussioncontrasting
confidence: 60%
“…One study found that 98.4% of obese women could be identified based upon the presence of this one bacterial species (SN) in amounts greater than 1.05% of total salivary bacteria. As this organism is capable of fermenting "indigestible" carbohydrates and extracting additional calories from fiber-containing foods, this may suggest that routine screening of saliva for this organism may provide significant clinical information regarding oral and systemic health risks among dental patients in routine care [16,17].…”
mentioning
confidence: 99%
“…Individuals with obesity present a constant inflammatory state; consequently, it is plausible to imagine that it impacts on the subgingival environment and influences local microbiota. Data from young adults with overweight or obesity without destructive periodontal disease demonstrated higher levels of the pathogenic species Tannerella forsythia and Porphyromonas gingivalis compared to normal-weight individuals with similar periodontal status [60]. Additional analysis of that study demonstrated that obesity parameters, such as waist circumference, hip circumference, and waist-hip ratio, had a significant positive association with P. gingivalis and Treponema denticola.…”
Section: Obesity and Periodontitis Associationmentioning
confidence: 79%
“…Thomas et al 15) conducted microbial analyses on 19 patients with periodontitis and showed that the periodontal state in obese subjects was far more deteriorated with a larger number of missing tooth and a higher score of periodontal-support loss as well as a higher level of the Capnocytophaga genus. In de Andrade et al 16) , conducted on 29 healthy, 26 overweight and 22…”
Section: Discussionmentioning
confidence: 99%